Random amplified polymorphic DNA-PCR typing of Vibrio parahaemolyticus isolated from local cockles (Anadara granosa) - Bilung, Lesley Maurice; Radu, Son; Bahaman, Abdul Rani; Abdul Rahim, Raha; Napis, Suhaimi; Cheah, Yoke Kqueen; Murugaiah, Chandrika; Abdul Hadi, Yousr; Robin, Tunung; Nishibuchi, Mitsuaki (Science Publications, 2005)
Randomly amplified polymorphic DNA (RAPD) was used in this study to examine the genetic relatedness among the Vibrio parahaemolyticus strains. In the analysis by RAPD-PCR, the size for RAPD fragments ranged from 0.25 to 10.0 kb with average number of ten bands. The RAPD profiles revealed a high level of DNA sequence diversity within the Vibrio parahaemolyticus strains tested. Hence, this study, demonstrated that the local cockles (Anadara granosa) in the study area are populated by genetically polymorphic strains of V. parahaemolyticus. In addition, RAPD-PCR is simple, robust and sensitive typing methods to differentiate the V. parahaemolyticus strains.